2017
DOI: 10.1161/circulationaha.117.029479
|View full text |Cite
|
Sign up to set email alerts
|

The Fluid Mechanics of Transcatheter Heart Valve Leaflet Thrombosis in the Neosinus

Abstract: Although transcatheter aortic valve replacement thrombosis is a multifactorial process involving foreign materials, patient-specific blood chemistry, and complex flow patterns, our study indicates that deployed THV geometry may have implications on the occurrence of thrombosis. In addition, a supraannular neosinus may reduce thrombosis risk because of reduced flow stasis. Although additional prospective studies are needed to further develop strategies for minimizing thrombus burden, these results may help iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 177 publications
(147 citation statements)
references
References 33 publications
8
136
1
2
Order By: Relevance
“…1a), not allowing the formation of strong enough recirculation zone in the sinuses to assist a faster closing of the leaflets. 23 This design feature will be addressed accordingly in the next design iteration.…”
Section: Discussionmentioning
confidence: 99%
“…1a), not allowing the formation of strong enough recirculation zone in the sinuses to assist a faster closing of the leaflets. 23 This design feature will be addressed accordingly in the next design iteration.…”
Section: Discussionmentioning
confidence: 99%
“…For the pre‐TAVR measurements, the aortic annulus was defined as the virtual plane connecting the basal insertion points of the three aortic valve leaflets . Since the leaflets are not visible on post‐TAVR data, the annular plane was defined by the plane that intersects the bottom of all three aortic sinuses . In both the pre‐TAVR and post‐TAVR measurements, the following planes were defined perpendicular to the centerline: the LVOT plane was defined 4 mm below the annulus; the sinus plane was defined at the largest dimension of the sinus of Valsalva (SOV), the STJ was defined as the plane connecting the points at which the SOV transitions to the ascending aorta; and the ascending aorta plane was defined at 10 mm above the STJ.…”
Section: Methodsmentioning
confidence: 99%
“…7 Though some studies have shown higher longterm survival rates in patients with increased surgical risk who undergo TAVR versus surgery, 4 complications including subclinical thrombus formation, paravalvular leakage, prosthesis migration/embolization, stroke, permanent pacemaker, and coronary occlusion have motivated numerous in vitro and in silico studies to provide greater understanding and improve clinical practice. [8][9][10][11][12][13][14][15][16] To facilitate further research and investigation into the hemodynamic profiles of the post-TAVR aortic root, a greater understanding of how aortic root geometry changes after TAVR is imperative. Current research utilizes a heterogeneous mix of aortic root geometries of healthy patients, untreated AS patients and patients that have been indicated for TAVR.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in vitro experimental testing such as the one presented in this study can be used to validate and verify the computational simulations (46)(47)(48)(49). The geometric confinement of TAVs disturbs the natural flow field between the leaflets and aortic sinuses, increases the blood residence time (stasis) on the leaflets, and consequently increases the likelihood of thrombogenesis on the TAV leaflets (58)(59)(60)(61)(62). For instance, regions of blood stagnation provide an opportunity for platelets and blood proteins to accumulate to critical concentrations leading to thrombosis (50)(51)(52)(53)(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 91%